Libro Libre Beginning Spanish - Huebener, Erin; Steinberg, Jessica; Open Textbook Library (Open Textbook Library, 2018)
One of the most important things we can do to hold ourselves accountable for our learning is to engage in goal setting and metacognition-a fancy term for thinking about the way we think and learn. The goals we set should be specific and achievable. Something like "Speak Spanish" is too broad, we need to focus on the steps we need to take to get there and the signs that we will see as proof of our progress.
Lectura cultural: La Patagonia -- Lectura cultural: Las cabeza colosales -- Lectura cultural: -AR verbs -- Lectura cultural: The Verb ir and Places -- Lectura cultural: Food -- Lectura cultural: Health and the Human Body -- Lectura cultural: Saber versus conocer -- Lectura cultural: Childhood and Adolescence -- Lectura cultural: Vacation -- Lectura cultural: The Present Perfect
In English.
Description based on online resource
Keywords: Language and languages -- Textbooks